Selection of Components and Methods of Modification of Soil Cement to Improve the Performance Properties of Subgrade - Hromova, O. V. (Science and Transport Progress, 2024)
Purpose. The main objective of the scientific article is a reasonable selection of soil-cement reinforcing structural elements and methods of modifying the soil-cement structure to strengthen the subgrade for railroad tracks. Methodology. For the construction of soil-cement reinforcing elements for a combined railway track using drilling and mixing technology, a number of tasks were solved, including: a reasonable selection of the components and modifiers of the soil-cement element; determination of the properties of the components; establishment of operational requirements for soil-cement and its composition; design of optimal compositions with specified performance characteristics, taking into account the properties of soils and operating modes. Findings. The influence of soil-cement components on the rheological properties of soil-cement mixtures and the physical and mechanical properties of soil-cement was studied. Based on the data processing by statistical analysis, the optimal content of the constituent components of soil-cement mixtures was selected to ensure the technological and operational performance of soil-cement for different types of soils and to strengthen the soil base during track construction. The influence of mineral granular, fibrous and chemical modifiers on the properties of soil cement was investigated. Originality. The possibility of using vertical reinforcing elements made of soil cement with the necessary technological and operational parameters obtained by drilling and mixing technology to strengthen the subgrade, taking into account the stress-strain state and morphology of the soil bases, has been determined. Based on the study, the author made an attempt to select the components and develop optimal soil cement compositions for strengthening the subgrade of a railroad for a combined track. The directions of modification of soil cement with mineral, fiber and chemical additives are also considered. Practical value. The study makes it possible to obtain soil-cement elements of optimal composition and properties for different types of soils and stress-strain states in order to vertically strengthen the soil bases for the railway track. To modify the structure of soil cement and minimize cement consumption, it is proposed to use fiber fibers as modifying reinforcement components. To increase the density, crack resistance, strength, and modulus of deformability and improve the plasticity of the mixture, it is recommended to use chemical modifiers up to 0.3 % and to save cement – particles of fine industrial waste in the form of ground slag or stone grinding screenings in the amount of 20...30 %.